Late pregnancy reversal from excessive gestational weight gain lowers risk of childhood overweight—A cohort study. (13th May 2013) - von Kries, Rüdiger; Chmitorz, Andrea; Rasmussen, Kathleen M.; Bayer, Otmar; Ensenauer, Regina
<x xml:space="preserve">Abstract</x> Objective Whether reversal to adequate gestational weight gain (GWG) in the third trimester reverses the risk for childhood overweight associated with excessive GWG is assessed. Design and Methods In a retrospective cohort study in 6, 665 mother–child pairs, pre‐pregnancy weight and the temporal course of GWG were collected from medical records. Overweight as defined by International Obesity Task Force was assessed at a mean age of 5.8 years. Main exposures were exceeding week‐specific cut‐off values for GWG in the third trimester or any previous trimester. Logistic regression models, adjusted for possible confounding factors, were used to predict the risk of childhood overweight from excessive GWG in the third trimester with stratification by excessive GWG in previous trimesters. Results In the final model, women who avoided excessive GWG in the third trimester had children with a 31% (odds ratio [OR]: 0.69, 95% confidence interval [CI]: 0.59, 0.82) lower probability being overweight. A similar association was observed for reversing from excessive GWG in the first or second trimester to normal GWG in the third trimester: 27% (OR: 0.73, 95% CI: 0.53, 0.99). Conclusions Avoidance of excessive GWG in the third trimester is associated with lower risk of childhood overweight even in case of excessive GWG in the first or second trimester.